ENT600 : Multi purpose shoes / Hasrul Hanif Harith … [et al.] - Harith, Hasrul Hanif; Mazlan, Intan Nooramira; Mawardi, Mohammad Shah Iskandar; Roslan, Mohd Khairul Fitri; Abu Bakar, Nuur Fazliyana (2015)
Based on the observation, we have found that injury occurs when misused of shoe soles with an appropriate technique and condition of ground surface. In addition, we did not know the condition of our cardiovascular system, which is good or bad with regular shoes. Thus, we create a product which can solves the misused of shoe soles and know our body health condition.